PREPRATION OF SESAME SEED PROTEIN ISOLATE AND STUDYING THE EFFECT OF ENZYMTIC HYDROLYSIS IN ANTIOXIDANT ACTIVITIES - & Shakir, Kadhim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
Sesame protein isolate (SPI) was prepared from dehulled, defatted sesame protein concentrate (SPC) using alkaline extraction and isoelectric precipitation. The optimum conditions for SPI preparation were “pH 12, sample to solvent ratio 1:30 (w/v), extraction temperature 60 ⁰C and extraction time 60 minutes”. The protein recovery using the conditions above was 63.83% with 90.05% of protein content and low oil content (0.05%). The optimum conditions for protein isolate hydrolysate preparation (depending on antioxidant activity) was achieved using trypsin (2000 U/gm) for 2 hours hydrolysis followed by hydrolysis with pepsin (1000 U/gm) for one hour at 37C⁰, which gave bitterness-free hydrolysate. The antioxidant activates for selected hydrolysates (free of bitterness) ranged from (23.95-49.22%) and (0.078-1.07) nm in Hydroxyl radical scavenging activity and metal chelating agent test respectively.